2002
DOI: 10.1016/s0301-0546(02)79081-2
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to local anaesthetics in dentistry. Myth or reality?

Abstract: Twenty-five adverse reactions were diagnosed, representing 0.5 % of the study population. None of these reactions was due to an allergic cause. Most (22/25) were mild, quickly reversible psychogenic or vasovagal reactions. One case was related to defects in the anesthetic technique. In two further cases, allergic etiology was ruled out after skin and dose provocative challenge tests with the anesthetic. In conclusion, allergic reactions to LA are very rare. Most adverse reactions are psychogenic or vasovagal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 19 publications
2
39
0
5
Order By: Relevance
“…The main advantage of Articaine is its better haemostatic and bone diffusibility but the drawback of Articaine is paresthesia. There is absolutely no scientific evidence available to support the claim that Articaine is associated with a greater incidence of paresthesia [5,10,11,31]. However further studies on a larger group of population are recommended for greater authenticity of this relatively new drug in oral and maxillofacial surgery in India to make as popular and safer to be used as a routine anesthetic agent in dentistry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantage of Articaine is its better haemostatic and bone diffusibility but the drawback of Articaine is paresthesia. There is absolutely no scientific evidence available to support the claim that Articaine is associated with a greater incidence of paresthesia [5,10,11,31]. However further studies on a larger group of population are recommended for greater authenticity of this relatively new drug in oral and maxillofacial surgery in India to make as popular and safer to be used as a routine anesthetic agent in dentistry.…”
Section: Resultsmentioning
confidence: 99%
“…Today it is considered as a reference standard against which other local anesthetic agents are compared. Various studies have been done in dentistry evaluating the safety and efficacy of Articaine [10,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Since its introduction in 1969, Articaine has gradually become implanted in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological reactions to local anaesthetics, particular the newer amides, however, remain anecdotal and symptoms usually result from vasovagal episodes or anxiety reactions (178,(181)(182)(183). Acute disorientation or seizures may occur after overdosage or inadvertent intravenous injection.…”
Section: Local Anaestheticsmentioning
confidence: 99%
“…Indeed, it has been suggested that true allergic reactions to local anaesthetics do not occur or are a myth. 8 However, there are multiple single-case reports of individual cases in the literature. [9][10][11][12][13] It has been estimated that true immunologic adverse reactions occur in approximately 1% of all adverse systemic reactions.…”
Section: Introductionmentioning
confidence: 99%